The Impact of Different Predictive Accounting Methods on Firm Performance - Yin, Yue; Zhang, Xuheng (International Journal of Global Economics and Management, 2024)
This study investigates the impact of various predictive accounting methods on firm performance. Predictive accounting, as an advancement from traditional accounting, enables managers to make more informed decisions by forecasting future financial metrics, thus enhancing resource allocation, risk management, and competitive positioning. Through a literature review of international studies, this paper examines predictive methods such as cash flow forecasting, historical trends, regression analysis, Monte Carlo simulations, and big data analytics. The study highlights how different predictive accounting approaches contribute to overall firm performance and presents practical insights for managers in choosing appropriate predictive methods aligned with firm-specific goals and market dynamics.